2015
DOI: 10.1038/npjbcancer.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survivors are at an increased risk for osteoporotic fractures not explained by lower BMD: a retrospective analysis

Abstract: Background:An association between higher bone mineral density (BMD) and the diagnosis of breast cancer (BC) has been reported. Data on the risk of osteoporotic fractures in women with BC are conflicting.Aims:The objective of this study was to assess fracture risk adjusted for BMD in women with and without BC, and to assess whether fracture risk in BC patients is attributed to BMD or BC characteristics.Methods:Using electronic medical records of patients who underwent dual energy X-ray absorptiometry BMD studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The increased awareness about CTIBL has led to guidelines and expert panel to recommend to monitor for bone loss with BMD by DXA (107). However in a retrospective study on 17,110 breast cancer survivor followed about 5 years demonstrated that the increased risk of a fracture was not explained by worse BMD suggesting that BMD does not adequately capture bone strength determinants as shown in other studies (108). When postmenopausal women with breast cancer treated with aromatase inhibitors were randomised to receive placebo or denosumab, the risk of all fracture in placebo group and the risk of fracture reduction in denosumab group were substantially independent of BMD (104).…”
Section: Hypogonadismmentioning
confidence: 99%
“…The increased awareness about CTIBL has led to guidelines and expert panel to recommend to monitor for bone loss with BMD by DXA (107). However in a retrospective study on 17,110 breast cancer survivor followed about 5 years demonstrated that the increased risk of a fracture was not explained by worse BMD suggesting that BMD does not adequately capture bone strength determinants as shown in other studies (108). When postmenopausal women with breast cancer treated with aromatase inhibitors were randomised to receive placebo or denosumab, the risk of all fracture in placebo group and the risk of fracture reduction in denosumab group were substantially independent of BMD (104).…”
Section: Hypogonadismmentioning
confidence: 99%
“…It was suggested that BC survivors are at an increased risk of fracture. Hazard ratio (HR) for any osteoporotic fracture in women with BC was 1.34 (P = 0.026) that was not explained by bone mineral density (BMD) but other processes that affect bone quality such as obesity [18] . In a single-centre, cross-sectional study examining the association of fat body mass with vertebral fractures in postmenopausal women with BC, Pedersini et al stratified participants treatment according to whether they were aromatase inhibitor naive or had been taking aromatase inhibitors for at least 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…All 5 studies examined the association between BMI and fracture risk [18] , [19] , [20] , [21] , [22] . Two studies were from the US [20] , [22] , one from Italy [19] , one from Israel [18] and one from China [21] . All studies were conducted among mature females with breast cancer (over 18).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 4 studies fulfilling all inclusion criteria were reviewed. [20][21][22][23] One was from China, 1 from Taiwan, 1 from the UK, and 1 from Israel. These studies involving 127,722 participants were identified for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Fraenkel et al [20] performed a case control cross-sectional, retrospective study to determine whether breast cancer was associated with osteoporotic fracture in 17,110 women with a BMD test between 2003 and 2011. Among 1,193 women with osteoporosis, 62 had a previous history of breast cancer while the remaining 131 did not.…”
Section: Resultsmentioning
confidence: 99%